2015
DOI: 10.1007/s11060-015-1958-z
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of bevacizumab and erlotinib after radiation and temozolomide in MGMT unmethylated GBM patients

Abstract: Survival for glioblastoma (GBM) patients with an unmethyated MGMT promoter in their tumor is generally worse than methylated MGMT tumors, as temozolomide (TMZ) response is limited. How to better treat patients with unmethylated MGMT is unknown. We performed a trial combining erlotinib and bevacizumab in unmethylated GBM patients after completion of radiation (RT) and TMZ. GBM patients with an unmethylated MGMT promoter were trial eligible. Patient received standard RT (60 Gy) and TMZ (75 mg/m2 × 6 weeks) after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…Although studies of new drugs take more time and are more laborious, they are also extremely important and largely conducted worldwide. New drugs for GBM treatment, such as bevazicumab, erlotinib (Raizer et al, 2016), 1,3-bis (2-chloroethyl)-1 nitrosourea (BCNU) (Vinjamuri et al, 2009), and gliadel (Xing et al, 2015), are being massively exploited with good results and some of them have already reached phase II clinical trials. In phase III trials, the implantation of gliadel and BCNU wafers in the after surgery tumor bed was assessed and improved overall survival average in 2 months (Westphal et al, 2003).…”
Section: New Therapies and Future Prospectivementioning
confidence: 99%
“…Although studies of new drugs take more time and are more laborious, they are also extremely important and largely conducted worldwide. New drugs for GBM treatment, such as bevazicumab, erlotinib (Raizer et al, 2016), 1,3-bis (2-chloroethyl)-1 nitrosourea (BCNU) (Vinjamuri et al, 2009), and gliadel (Xing et al, 2015), are being massively exploited with good results and some of them have already reached phase II clinical trials. In phase III trials, the implantation of gliadel and BCNU wafers in the after surgery tumor bed was assessed and improved overall survival average in 2 months (Westphal et al, 2003).…”
Section: New Therapies and Future Prospectivementioning
confidence: 99%
“…For the leading representatives of this group, erlotinib, gefitinib, afatinib, and lapatinib, trials have not shown efficacy either alone or in combination. Erlotinib showed no efficacy and unacceptable side effects as a single agent in newly diagnosed glioblastoma [ 25 ] and later studies combining it for recurrent glioblastoma with mechanistic target of rapamycin (mTOR) blockers or bevacizumab were unsuccessful [ 26 28 ]. Gefitinib did not result in improved overall survival in a phase II trial in recurrent glioblastoma [ 29 ] or in a phase I/II trial in combination with radiation in newly diagnosed glioblastoma [ 30 ].…”
Section: Egfr Targeting Agentsmentioning
confidence: 99%
“…Additional phase 2 trials have evaluated bevacizumab in combination with irinotecan, cetuximab, carboplatin, etoposide, fotemustine, sorafenib, temozolomide, erlotinib, panobinostat, and temsirolimus [66,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88]. There have also been trials evaluating bevacizumab and re-irradiation [89][90][91].…”
Section: Recurrent Glioblastomamentioning
confidence: 99%